Steiner/Waldorf Schools in Australia: The List - Paull, John (Advances in Social Sciences Research Journal, 2026)
Dr Rudolf Steiner (1861-1925) and Emil Molt (1876-1936) together founded the original Waldorf School in Stuttgart in 1919 in the turmoil of post-WWI Germany. The project was a marriage of Steiner’s pedagogy and Molt’s funding. The Stuttgart school was to serve as a prototype for a new alternative education movement. Since then, Steiner schools (aka Waldorf schools) have proliferated across the globe (with 3142 schools and kindergartens in 74 countries). In Australia there are 62 Steiner schools with a total enrolment of 11,391 students. The mean number of students per school is 184 and the median is 150 students. There are Steiner schools in all six Australian states (NSW, n=21; Victoria, n=16; Queensland, n=8; Western Australia, n=8; South Australia, n=4; Tasmania, n=2), and in the two territories (Northern Territory, n=2; Australian Capital Territory, n=1). One third of Steiner schools in Australia offer the full spectrum of primary plus secondary classes (i.e. K-12) (n-21); a further third of Steiner schools offer the spectrum of primary classes (i.e. K-6) (n=21); a final third of Steiner school (n=20) offer some other variation of classes. Of the 62 Steiner schools in Australia, 41 are differentiated with either the name ‘Steiner’ (n=34) or ‘Rudolf Steiner’ (n=7); a small number bear the name ‘Waldorf’ (n=4); some others are not differentiated by either ‘Steiner’ nor ‘Waldorf’ (n=8); in addition, some State schools offer a ‘Steiner stream’ nested within a government school (n=9). Most schools in Australia are government schools (n=6,727) followed by Catholic schools (n=1,759), plus there is a multitude of other religious schools (aka faith-based schools). Steiner schools (n=62) lead the field of the ‘alternative’ schools in Australia, followed by Montessori schools (n=46), and ‘other’ (n=47). In the present paper the list of Australia’s 62 Steiner schools includes name, state or territory, enrolment, and NAPLAN participation.